Channeling the Concern for Education, Strengthening the Unity by Serving the Community - Harahap, Hasriyati; Savitri, Intan; Nst, M Rezi Syahbanda (The Future of Education Journal, 2025)
This research discusses the role of higher education institutions in community service as the implementation of the Tri Dharma of Higher Education, particularly in the fields of education and social welfare. Through the community service activities in Kota Pari Village, this study explores the interaction between students and the community in identifying and seeking solutions to social problems. The results of the study indicate that this service not only strengthens social relationships but also provides valuable experiences for students in understanding social realities. Additionally, this activity serves as an effective means for the application of knowledge and the development of leadership character and social awareness. This research is expected to serve as a basis for the development of more effective and sustainable community service programs in the future.